2011
DOI: 10.1002/gcc.20888
|View full text |Cite
|
Sign up to set email alerts
|

Relative 8q gain predicts disease‐specific survival irrespective of the TMPRSS2‐ERG fusion status in diagnostic biopsies of prostate cancer

Abstract: Screening tools have greatly improved prostate cancer (PCa) detection, but the disease course is heterogeneous, and standard clinicopathological parameters do not fully discriminate aggressive from indolent tumors. To evaluate the prognostic value of the TMPRSS2-ERG fusion gene combined with chromosome arm 8q relative gain in diagnostic biopsies of PCa, we studied a consecutive series of 200 diagnostic needle biopsies from patients with 10-year disease-specific survival data. TMPRSS2-ERG fusion gene status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…Five-micrometer-thick sections of formalin fixed, paraffin-embedded (FFPE) prostatectomy specimens were processed and hybridized as previously described [22], [23], [34]. For the relative 8q24 gain assessment, a commercial dual-color break-apart probe flanking MYC at 8q24 (ZytoVision, Bremerhaven, Germany) and a centromeric probe for chromosome 18 (CEP18) labeled with SpectrumAqua (Vysis, Downers Grove, IL, USA) were used, as previously described [22], [23], [34].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five-micrometer-thick sections of formalin fixed, paraffin-embedded (FFPE) prostatectomy specimens were processed and hybridized as previously described [22], [23], [34]. For the relative 8q24 gain assessment, a commercial dual-color break-apart probe flanking MYC at 8q24 (ZytoVision, Bremerhaven, Germany) and a centromeric probe for chromosome 18 (CEP18) labeled with SpectrumAqua (Vysis, Downers Grove, IL, USA) were used, as previously described [22], [23], [34].…”
Section: Methodsmentioning
confidence: 99%
“…For the relative 8q24 gain assessment, a commercial dual-color break-apart probe flanking MYC at 8q24 (ZytoVision, Bremerhaven, Germany) and a centromeric probe for chromosome 18 (CEP18) labeled with SpectrumAqua (Vysis, Downers Grove, IL, USA) were used, as previously described [22], [23], [34]. Slides were counterstained with DAPI (Vector Laboratories, Burlingame, CA, USA) and fluorescent signals were captured in a Zeiss Axioplan fluorescence microscope (Zeiss, Oberkochen, Germany) coupled with a Cohu 4900 CCD camera using a Cytovision system version 7.4 (Leica Biosystems Richmond, Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many groups have analyzed the presence of TMPRSS2:ERG fusion or ERG protein expression in prostate cancer cohorts with variable outcome [8092]. Barros-Silva et al used fluorescent in situ hybridization (FISH) to detect TMPRSS2-ERG rearrangement in a cohort of 200 biopsies and found an association with low PSA levels at diagnosis and low Gleason score [93]. In needle-biopsies immunohistochemical ERG detection can be used to discriminate prostate cancer from its mimickers, although the additional value to other markers such as p63, basal cell keratin 5, and AMACR is limited [92, 9499].…”
Section: Molecular Markersmentioning
confidence: 99%
“…c-MYC is amplified in approximately 70% of clinical prostate cancer [93, 110, 111]. Ribeiro et al found that patients with gain of MYC gene copy numbers in a group of 60 prostate cancer needle-biopsies using FISH were significantly at risk for disease-specific death [110].…”
Section: Molecular Markersmentioning
confidence: 99%